The prostatic utricle: An under-recognized condition resulting in significant morbidity in boys with both hypospadias and normal external genitalia. Issue 5 (October 2017) - Hester, Austin G.; Kogan, Stanley J.
Summary: Introduction: Pediatric presentations of a prostatic utricle have received only scant attention. Though recognized with increased frequency in boys with hypospadias, little is described about their incidence and potential for morbidity in boys with normal external genitalia. Methods: We initially reviewed a cohort of 64 patients with hypospadias seen over a 3-year period to determine the frequency of investigative lower urinary tract studies and utricle identification. Children with disorders of sexual differentiation were excluded from this review. A subsequent group of 70 boys with hypospadias and 23 boys with normal external genitalia presenting with lower urinary tract symptoms (LUTS) who were found to have an unsuspected utricle were reviewed. This comparative group was investigated since symptomatology was the indication for evaluation, contrasting with those in the hypospadias group who were investigated because of hypospadias presence alone. Results: In our initial review of 64 patients only 24 (37.5%) underwent an investigative study and six (9.4%) had a utricle. Three (50%) required surgical excision, allowing their hypospadias repair to proceed. Results in the subsequent group with hypospadias confirmed these findings with increased rates of investigation and identification. The boys with normal external male genitalia all required surgery since symptoms were the result of the utricle alone. Penile pain with voiding, hematuria, epididymitis, and urinary infection were the most common causes for interventions. Conclusions: The prostatic utricle should be considered as a cause of morbidity in boys with both normal external genitalia and those with hypospadias. Endoscopic or radiological evaluation (see Figure) should be undertaken in all boys with proximal hypospadias, boys with hypospadias and associated cryptorchidism, and those with hypospadias with associated urinary symptoms. Boys with normal external genitalia with lower urinary tract symptoms not explained with imaging should undergo cystoscopy, as an unidentified unsuspected utricle may be the underlying cause.Figure. A prostatic utricle is identified via voiding cystourethrogram.